2018
DOI: 10.1177/0300060518769524
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum S100A1 level and Global Registry of Acute Coronary Events score in patients with non-ST-segment elevation acute coronary syndrome

Abstract: ObjectiveAcute coronary syndrome (ACS) is associated with several clinical syndromes, one of which is acute non-ST-segment ACS (NSTE-ACS). S100A1 is a calcium-dependent regulator of heart contraction and relaxation. We investigated the association between the serum S100A1 level and the Global Registry of Acute Coronary Events (GRACE) risk score in patients with NSTE-ACS and the potential of using the serum S100A1 level to predict the 30-day prognosis of NSTE-ACS.MethodsThe clinical characteristics of 162 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Based on previous work, 14 we retrospectively reviewed patients with AAD to examine the value of S100A1 in diagnosing AAD. The results suggested that the plasma concentration of S100A1 was significantly increased in patients with AAD and showed potential diagnostic value for AAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous work, 14 we retrospectively reviewed patients with AAD to examine the value of S100A1 in diagnosing AAD. The results suggested that the plasma concentration of S100A1 was significantly increased in patients with AAD and showed potential diagnostic value for AAD.…”
Section: Discussionmentioning
confidence: 99%
“… 13 S100A1 can serve as an early diagnostic marker of ischemic coronary artery disease in patients with acute myocardial infarction. 14 However, few studies have evaluated S100A1 as a biomarker in patients with AAD. Therefore, in this study, an elevated S100A1 level was used as a marker of AAD to explore its diagnostic value in patients with AAD.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Stamatelopoulos et al on amyloid-β (1-40) and Li et al on serum S100A1 found that these biomarkers may help the prognosis in clinical risk scoring, such as GRACE and TIMI, which are defined as mortality predictors in ACS guidelines [7][8]. In the present study, Netrin-1 levels measured at the time of presentation to the hospital were found to be significantly different in the medium and high-risk GRACE groups as compared with the low-risk group (p = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various markers are evaluated to demonstrate the success of reperfusion and reduced ischemia [5][6]. It has been shown that clinical risk scores, such as Global Registry of Acute Coronary Events (GRACE) and Thrombolysis in Myocardial Ischemia (TIMI), which have significant distinguishing power in calculating the hospital mortality risks, hospital discharge, and six-month mortality risks mentioned in ACS guidelines, can be improved with some biomarkers and new parameters [7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation